Analysis of dipolar relaxation in polyurethane/polyaniline blend - Malmonge, J. A.; Dos Santos, M. A.; Sakamoto, W. K. (Springer, 2005)
Thin films of blend made up of castor oil-based polyurethane (PU) and polyaniline (PANI) were obtained by casting. The molecular mobility was studied using dielectric spectroscopy and thermally stimulated depolarization current (TSDC) for blends with two different compositions (90/10, 80/20) and the results were compared with PU pure. The peak located around -60 degrees C in TSDC thermograms of PU/PANI blend has dipolar behavior and might be attributed to the change in the molecular chain due to the interaction between isocyanate and the solvent. Vogel-Fulcher Tammann fits was performed on the observed relaxation and the result shows a alpha-relaxation-like. (c) 2005 Springer Science + Business Media, Inc.